Autoimmune retinopathy: A case report from India - Ganesh, Sudha K. (Oman J Ophthalmol, 2017)
A first case report of autoimmune retinopathy (AIR) from India. A middle-aged female patient presented with subacute loss of vision in both eyes. Clinical examination revealed a near normal fundus in both the eyes. A presumed diagnosis of nonparaneoplastic AIR was made based on clinical features and suggestive investigations. Early detection and management with steroids or immunosuppression may be beneficial to patients with AIR.